Studies on occurrence, molecular detection and genotyping of Cryptosporidium parvum along with associated risk factors in cattle and human from Aizawl district, Mizoram, India. Issue 2 (17th February 2020) - Das, P.; Deka, Devajani; Borthakur, S. K.; Roychoudhury, P.; Das, M.
ABSTRACT: An epidemiological study was conducted along with molecular detection of Cryptosporidium in cattle and human from Aizawl district of Mizoram, India. A total of 200 samples (100 each of cattle faeces and human stool) were collected randomly for detection of Cryptosporidium ocysts by mZN staining after concentration of ocysts by Sheather's sucrose floatation technique. Genomic DNA was extracted from the microscopically positive faecal/stool samples for PCR-based detection of 18S (SSU) rRNA gene of Cryptosporidium . All the microscopically positive cattle faecal and human stool samples were found to be positive for 18S (SSU) rRNA gene of Cryptosporidium, and subsequently the species and genotype of Cryptosporidium were detected by PCR- restriction fragment length polymorphism (RFLP). The overall prevalence rates of Cryptosporidium were 13% and 5% in cattle and human, respectively. Significantly ( P < 0.01) higher prevalence rate of Cryptosporidium was recorded in 0–6 months than above 6 months of age group of cattle. The sex-wise and breed-wise prevalence rates of Cryptosporidium did not vary significantly in both cattle and human. Diarrhoeic cattle and human were found to be significantly ( P < 0.01) more infected with Cryptosporidium than non-diarrhoeic. Significantly ( p < 0.05) higher prevalence rates of Cryptosporidium were found in cattle during monsoon season than winter, and the seasonal variation was non-significant in human. The PCR-RFLP revealed C. parvum (genotype II) in nine numbers and C. andersoni in four numbers of cattle faecal samples and the two numbers of human stool samples revealed genotype I and genotype II, one each.